A study of prescribing pattern of antihypertensive drugs in hypertensive patients with co morbid diabetes in a tertiary care teaching hospital - Sharma, Jay Kumar; Parmar, Shailesh P.; Trivedi, Hiren R. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Hypertension and diabetes mellitus are among the commonest non-communicable diseases. Co-existence of hypertension and diabetes increases morbidity and mortality. So co-existence of these diseases requires attention and rational management. Studying current prescribing pattern of drugs provide data for recommendations and decisions regarding rational practice. We undertook this study to study prescribing pattern. Methods: It was cross sectional, observational, descriptive study in outdoor patients suffering from hypertension and type 2 diabetes mellitus for duration of one year. Data of 601 patients were analyzed using descriptive statistics to determine prescribing pattern of drugs. Results: In this study, 71.55% patients were above 50 years age. Female patients were 56.57%. Average duration of hypertension was 4.08 years. Commonly prescribed antihypertensive drug groups were angiotensin converting enzyme (ACE) inhibitors (85.36%) followed by β receptor blockers (33.44%) and calcium channel blockers (29.95%). Enalapril (85.36%) followed by amlodipine (29.95%) and atenolol (21.46%) were commonly prescribed antihypertensive drugs. Single antihypertensive drug was prescribed in 292 (48.59%) prescriptions. The most common monotherapy drug was enalapril (82.19%). Two antihypertensive drugs were prescribed in 231 (38.43%) prescriptions. The most common two drug combination was ACE inhibitors + β receptor blockers (40.69%). Four antihypertensive drugs were prescribed in only 1.50% prescriptions. Conclusions: From this study, the results suggest that the prescribing pattern of antihypertensive drugs reflects recommendations of current guidelines and practices. However, β receptor blockers were prescribed more commonly. There is room for improvement in choice of drugs.